Novel non-invasive 12-lead ECG-based imaging method with potential to guide and optimise right ventricular lead implantation. (19th May 2022) - Fruelund, PZ; Van Dam, P; Melgaard, J; Soegaard, P; Sommer, A; Lundbye-Christensen, S; Riahi, S; Zaremba, T; Graff, C
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Svend Andersens Foundation Karl G Andersens Foundation Helsefonden Background: Right ventricular (RV) pacing may induce electrical and mechanical dyssynchrony which may lead to heart failure. Often, the physician aims for lead implantation at the RV septum as this is expected to result in a more physiologic activation compared to alternative RV lead locations. Fluoroscopy, often in combination with QRS morphology derived from the 12-lead ECG, is used to guide lead implantation. However, this method is inaccurate and can result in a non-optimal RV lead location. We present a novel non-invasive method to create patient-specific 3D electrical activation maps from the 12-lead ECG that has potential to support RV lead implantation. Methods: Data from 34 patients with an implanted dual chamber pacemaker were used. A contrast-enhanced cardiac CT scan showing the RV lead implantation site was obtained as well as recording of a 12-lead ECG during RV pacing together with a 3D photo documenting the ECG electrode positions. Discrete patient-specific torso and heart models were created from the CT scans. Each torso model was merged with the 3D photo for precise placement of the ECG electrodes in relation to the heart (figure 1). Combining the 12-lead ECGs and the heart/torso models, patient-specific 3D electrical activation maps originating from the RV were created using a novel inverse-ECG technique applying electrophysiological rules. The accuracy of the inverse-ECG method was determined by comparing the earliest site of activation from the 3D activation map with the known RV insertion site marked on the CT scan. Results: Documented by the implanting physician in the medical records, 33 RV leads were estimated to be septal and one apical. Estimated from the CT scan 9 leads were placed septal, 18 apical and 7 on the free wall. The mean geodesic distance between the initial site of activation in the 3D activation map and the marked RV insertion site from CT was 13.6 ±5.7 mm (range 4.3-28.6). The distance for each patient is shown in figure 2. The initial site of activation was constrained to the discrete nodes of the ventricular model whereas the marker for RV lead position was localized freely on the CT scan. The average distance from the RV CT marker to the nearest discrete node was 4.3 ±2.2 mm. Correcting for this error, the geodesic distance between the initial site of activation and RV CT marker was 9.3 ±5.4 mm (range 0.0-24.6). The average time used for 3D activation map computation was 1.1 ±0.4 s per ECG. Conclusions: We demonstrated a novel non-invasive 12-lead ECG-based method to accurately and effectively localize the RV lead in relation to the ventricular anatomy during RV pacing. Furthermore, we confirmed that the RV lead was often implanted in an unintended position. With further advancements, this method has the potential to support physicians during pacemaker implantation to ensure optimal RV lead positioning. Further studies are needed to confirm the accuracy.